2021
DOI: 10.3390/ijerph182412958
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Heart Failure Patients with Severely Reduced Ejection Fraction during Cardiopulmonary Exercise Testing on Treadmill and Cycle Ergometer; Similarities and Differences

Abstract: Background: Peak oxygen consumption (VO2) measured by cardiopulmonary exercise testing (CPET) is a significant predictor of mortality and future transplantation in heart failure patients with severely reduced ejection fraction (HFrEF). The present study evaluated the differences in peak VO2 and other prognostic variables between treadmill and cycle CPETs in these patients. Methods: In this cross-over study design, thirty males with severe HFrEF underwent CPET on both a treadmill and a cycle ergometer within 2–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
(49 reference statements)
2
13
1
Order By: Relevance
“… 36 , 37 According to previous studies, cycle ergometer CPET is likely to underestimate VO 2peak compared to treadmill CPET. 38 , 39 However, for safety concerns, to prevent measurement errors and because of the clinical infrastructure in the Máxima MC, we used cycle ergometer CPET as gold standard. All CPETs were supervised by sports physicians or a human movement scientist, and conducted according to international standards.…”
Section: Methodsmentioning
confidence: 99%
“… 36 , 37 According to previous studies, cycle ergometer CPET is likely to underestimate VO 2peak compared to treadmill CPET. 38 , 39 However, for safety concerns, to prevent measurement errors and because of the clinical infrastructure in the Máxima MC, we used cycle ergometer CPET as gold standard. All CPETs were supervised by sports physicians or a human movement scientist, and conducted according to international standards.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon, together with the increase in catecholamines during the treadmill exercise and changes in blood flow distribution in HFrEF [ 20 ], may explain the higher HR on the treadmill and higher diastolic BP on the cycle ergometer. Regarding HRR-1, previous studies [ 22 , 23 , 24 ] reported disparate results. In our study, HRR-1 was better on the treadmill.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the ventilatory response, VE, RR, and BR reflected the higher ventilatory demand of the treadmill, although with a better ventilatory efficiency when analyzing PetCO 2 and EqO 2 /EqCO 2 . Of these parameters, only PetCO 2 had been studied in HFrEF by Mazaheri et al [ 24 ], although in a small sample of exclusively male patients ( n = 30) with significantly lower effort on the treadmill. These results highlight the importance of the exercise modality in ventilatory demand because the ventilatory response varies with the type of ergometer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations